2013
DOI: 10.1016/j.biombioe.2013.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Influence of organic matter on flocculation of Chlorella vulgaris by calcium phosphate precipitation

Abstract: Influence of organic matter on flocculation of Chlorella vulgaris by calcium phosphate precipitationBiomass and bioenergy, vol 54, 107-114.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
2
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 33 publications
2
33
2
3
Order By: Relevance
“…Autoflocculation by increasing the pH of the medium and electrolytic flocculation may be used to separate algae without the addition of chemicals and would be more economical than other harvesting techniques for marine microalgae [50,51]. Moreover, unlike other harvesting technologies, the cost contribution to algal lipid from electrolytic flocculation was unaffected by the concentration of algae in the algal water [52].…”
Section: High Capital and Operating Costs Hamper Commercial-scale Algmentioning
confidence: 99%
“…Autoflocculation by increasing the pH of the medium and electrolytic flocculation may be used to separate algae without the addition of chemicals and would be more economical than other harvesting techniques for marine microalgae [50,51]. Moreover, unlike other harvesting technologies, the cost contribution to algal lipid from electrolytic flocculation was unaffected by the concentration of algae in the algal water [52].…”
Section: High Capital and Operating Costs Hamper Commercial-scale Algmentioning
confidence: 99%
“…Because phosphate is a mineral resource with a limited supply, this flocculation method is unsustainable unless perhaps when microalgae are used for treating wastewaters with excessive phosphate concentrations. Beuckels et al (2013), however, showed that it is possible to recover the phosphate from the harvested biomass by dissolving the calcium phosphate through mild acidification.…”
Section: Autoflocculationmentioning
confidence: 96%
“…It is therefore recommended that investigations be carried out through pilot plant studies which involves continuous biomass harvesting and various unit operations and processes employed for mass microalgae cultivation. Some studies reported that flocculation of microalgae can occur spontaneously without the need for chemicals, referred to as autoflocculation which can be induced by increasing the medium pH [16]. According to Harith et al [17], harvesting efficiency of Chaetoceros calcitrans of higher than 90% was achieved by adjusting the culture pH to 10.2 using either NaOH or KOH.…”
Section: Correlation Of Zeta Potential Values and Flocculation Performentioning
confidence: 99%